Oscillation Kinetics of Post-illumination Increase in Chl Fluorescence in Cyanobacterium Synechocystis PCC 6803 - Xu, Min; Lv, Jing; Fu, Pengcheng; Mi, Hualing (Frontiers in Plant Science, 2016)
After termination of longer-illumination (more than 30 s), the wild type of Synechocystis PCC 6803 showed the oscillation kinetics of post-illumination increase in Chl fluorescence: a fast phase followed by one or two slow phases. Unlike the wild type, ndh-B defective mutant M55 did not show any post-illumination increase under the same conditions, indicating that not only the fast phase, but also the slow phases were related to the NDH-mediated cyclic electron flow around photosystem I (PS I) to plastoquinone (PQ).The fast phase was stimulated by dark incubation or in the presence of Calvin cycle inhibitor, iodoacetamid (IA) or cyclic photophosphorylation cofactor, phenazinemethosulphate (PMS), implying the redox changes of PQ by electrons generated at PS I reduced side, probably NAD(P)H or ferredoxin (Fd). In contrast, the slow phases disappeared after dark starvation or in the presence of IA or PMS, and reappeared by longer re-illumination, suggesting that they are related to the redox changes of PQ by the electrons from the photoreductants produced in carbon assimilation process. Both the fast phase and slow phases were stimulated at high temperature and the slow phase (P2) was promoted by response to high concentration of NaCl. The mutant M55 without both phases could not survive under the stressed conditions.